Peran Organizational Citizenship Behavior Sebagai Upaya Optimalisasi Kinerja Pegawai Berbasis Work-Life Balance - Fadil Gema Imani; Adya Hermawati; Bambang Budiantono (Universitas 45 Surabaya, 2023)
The purpose of this study was to determine the effect of work-life balance on employee performance mediated by organizational citizenship behavior. The population in this study were all employee at Technical Unit of Vocational Training Wonojati in Malang. The sampling technique in this study used